Progress in Medicine: Experts Take Stock. - PLOS Medicine Editors; Andrew Beck; Ewan Birney; Manuel Graeber; James Tumwine; Phillipa Hay; Hyeong Sik Ahn; Anushka Patel; Philipp du Cros; Lorenz von Seidlein; Nick Wareham; Nicola Low (PLoS Medicine)
In the year-end editorial, the PLOS Medicine editors ask 11 researchers and clinicians about the most relevant challenges, promising research, and important initiatives in their fields as we head into 2016.